The role of grit for college students in Indonesia - Dyantari, Kadek Ratih; Simarmata, Nicholas (Insight: Jurnal Ilmiah Psikologi, 2023)
One of the main foundations for the development of an individual’s quality and potential in all facets of life is education. Moreover, as one of the agents of bringing about positive change, college students must engage in a learning process that involves various roles that are fulfilled both academically and non-academically. College students are expected to be able to maximize every role in the process of successful achievement through grit, which is defined as persistence and passion. This study aimed to conduct a literature review on related studies in order to better comprehend grit and its importance for college students in Indonesia. Furthermore, ten studies that met the inclusion and exclusion criteria were included in the literature review. According to the results of the literature review, there are various roles of grit for college students in Indonesia. These various roles are related to subjective well-being, mindset, flourishing, self-adjustment, stress, academic procastination, academic accomplishment, resilience, coping strategies, and hope in college students. In addition, it was expected that this literature review may provide college students in Indonesia with knowledge concerning the role of grit and how to develop it, as it will have an impact on many aspects of life and success.